2022
DOI: 10.1002/cctc.202101873
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electroconversion CO2‐to‐Formate by Oxygen‐Vacancy‐Rich Ultrasmall Bi‐Based Catalyst Over a Wide Potential Window

Abstract: Bi-based materials quickly rise as promising candidates for electrochemical CO 2 -to-formate conversion. However, most of them only display a narrow potential range for the desired formate selectivity. Herein, we designed an oxygen-vacancy-rich ultrasmall bismuth subcarbonate supported on reduced graphene oxide composite (Vo-BOC/G) for electrochemical CO 2 -toformate conversion. The Vo-BOC/G exhibits an outstanding formate selectivity up to 100 % at À 1.2 V vs. RHE and an impressive partial current density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…[ 24 ] In the high‐resolution spectrum of O1s, the peaks at 529.5, 530.94, and 531.9 eV correspond to Bi─O, oxygen vacancy, and adsorbed water, respectively (Figure 1C). [ 25–27 ] The peak for oxygen vacancies gradually becomes stronger as the interface electron density increases (Figure 1B,C). The phenomenon was also confirmed by electron spin resonance (EPR) (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 ] In the high‐resolution spectrum of O1s, the peaks at 529.5, 530.94, and 531.9 eV correspond to Bi─O, oxygen vacancy, and adsorbed water, respectively (Figure 1C). [ 25–27 ] The peak for oxygen vacancies gradually becomes stronger as the interface electron density increases (Figure 1B,C). The phenomenon was also confirmed by electron spin resonance (EPR) (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…(b) FEs in the potential range from −0.8 to −1.8 V vs RHE. (c) Potential windows with FE HCOO– over 80% of the Bi NPSs and other Bi based catalysts reported in literature. ,, (d) Long-term stability test of Bi PNSs at −1.0 V vs RHE for 10 h.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of oxygen‐vacancy‐rich Bi subcarbonate with reduced graphene oxide (Vo‐BOC/G) has been designed for eCO 2 RR‐to‐formate conversion. [ 212 ] Using 0.1 m KHCO 3 , the Vo‐BOC/G shows 100% formate selectivity at −1.2 V versus RHE and boasts a partial current density of 38 mA cm −2 . It has been shown that the abundant V o defects lower the energy barrier for * CO 2 formation, which results in high formate selectivity.…”
Section: Advanced Electrocatalysts For Cathodic Reactionsmentioning
confidence: 99%